Radiative heat transfer exceeding the blackbody limit between macroscale planar surfaces separated by a nanosize vacuum gap - Michael P. Bernardi (Nature Portfolio, 2016)
Evanescent coupling between surfaces separated by a distance smaller than the thermal wavelength can lead to radiative heat transfer greater than the blackbody limit. Here, the authors demonstrate this between two macroscopic-scale surfaces, paving the way to harnessing the effect in thermal devices.